Effects of microhabitat on palm seed predation in two forest fragments in southeast Brazil - Fleury, M.; Galetti, M. (Elsevier B.V., 2004)
The establishment of plants depends crucially on where seeds are deposited in the environment. Some authors suggest that in forest understory seed predation is lower than in gaps, and higher than at the forest edge. However, most studies have been carried out in large forest patches and very little is known about the effects of microhabitat conditions on seed predation in forest fragments. We evaluated the effects of three microhabitats (gaps, forest edge, and understory) on seed predation of two palm species (Euterpe edulis and Syagrus romanzoffiana) in two semi-deciduous forest fragments (230 and 2100 hat in southeast Brazil. Our objective was to test two hypotheses: (1) Low rodent abundance in small fragments as a result of meso-predator action levels leads to lower seed predation in small fragments. (2) Most mammal species in small fragments are generalists with respect to diet and habitat, so that seed predation is similar in different microhabitats (gaps, forest edge and understory) in the small fragment, but not in the larger one. The study community of small fragments is usually composed of generalist species (in diet and habitat aspects), so we expected the same rate of seed predation among microhabitats (gaps, forest edge and understory) in the tested smaller fragment. The experiment was carried out in the dry season (for E. edulis) and in the wet season (for S. romanzoffiana) in 1999. We conclude that post-dispersal seed predation in forest fragments can be directly connected with mammal communities, reflecting their historical and ecological aspects. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: Atlantic forest; forest fragmentation; seed predation; microhabitat; palm; Euterpe edulis; Syagrus romanzoffiana